2014
DOI: 10.1093/mnras/stu449
|View full text |Cite
|
Sign up to set email alerts
|

The bright end of the galaxy luminosity function at z≃7: before the onset of mass quenching?

Abstract: We present the results of a new search for bright star-forming galaxies at redshift z 7 within the UltraVISTA DR2 and UKIDSS UDS DR10 data, which together provide 1.65 deg 2 of near-infrared imaging with overlapping optical and Spitzer data. Using a full photometric-redshift analysis to identify high-redshift galaxies and reject contaminants, we have selected a sample of 34 luminous (−22.7 < M U V < −21.2) galaxies with 6.5 < z < 7.5. Crucially, the deeper imaging provided by UltraVISTA DR2 confirms all of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
445
10
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(509 citation statements)
references
References 105 publications
(148 reference statements)
52
445
10
2
Order By: Relevance
“…2.1. Further, our model naturally predicts that the brightend of the UV LF at z 7 must be flatter than the usuallyassumed Schechter function and is compatible with both the HMF and the double power-law (DPL) slope estimated from the widest-area survey carried out so far at this redshift (Bowler et al 2014). Our model slightly over-predicts the number of bright galaxies at z 5 and z 6, as can be seen from the same figure.…”
Section: Understanding the Uv Lf Evolutionsupporting
confidence: 75%
See 1 more Smart Citation
“…2.1. Further, our model naturally predicts that the brightend of the UV LF at z 7 must be flatter than the usuallyassumed Schechter function and is compatible with both the HMF and the double power-law (DPL) slope estimated from the widest-area survey carried out so far at this redshift (Bowler et al 2014). Our model slightly over-predicts the number of bright galaxies at z 5 and z 6, as can be seen from the same figure.…”
Section: Understanding the Uv Lf Evolutionsupporting
confidence: 75%
“…Bouwens et al 2007;McLure et al 2009;Bouwens et al 2010a;McLure et al 2010;Oesch et al 2010b;McLure et al 2013) while ground-based widefield surveys such as UltraVISTA are revealing luminous galaxies populating the bright-end of the UV LF at z 7 (e.g. Ouchi et al 2010;Bowler et al 2012Bowler et al , 2014. Spectral energy distribution (SED) fitting to broad-band photometry has also been used to build galaxy stellar mass functions (SMF; González et al 2011), understand the stellar populations in these sources through their UV (β) slopes (Bouwens et al 2010b;Finkelstein et al 2012;Wilkins et al 2011;Dunlop et al 2012Dunlop et al , 2013Bouwens et al 2013;Rogers et al 2014), infer their physical properties (Oesch et al 2010a;Labbé et al 2010a;McLure et al 2011;Labbé et al 2013) and calculate the growth of stellar mass density (SMD) with redshift (Labbé et al 2010a;González et al 2011;Stark et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7. At z;7 and 8, the faint end (M UV −16) data has been collected using the lensed Hubble Frontier fields (HFF; Atek et al 2015;Livermore et al 2016), while the brightest galaxies have been detected using ground-based Ultra-Vista surveys (e.g., Bradley et al 2014;Bowler et al 2014); (unlensed) HST data has been used to obtain the z;9 UV LF as shown in the same figure.…”
Section: Faint End Of the Uv Luminosity Functionsmentioning
confidence: 99%
“…Over the past few years, ground-and space-based observations have allowed a statistically significant data set to be collected for z;6-10 Lyman Break galaxies (LBGs; Bouwens et al 2010Bouwens et al , 2011Bouwens et al , 2015bCastellano et al 2010;McLure et al 2010McLure et al , 2013Oesch et al 2010Oesch et al , 2013Oesch et al , 2016Bradley et al 2012;Bowler et al 2014Bowler et al , 2015Atek et al 2015;Livermore et al 2016). In this work, our aim is to revisit the constraints allowed on the WDM particle mass by combining these "galaxy" data sets with the latest limits on the cosmological electron scattering optical depth inferred by Planck.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies find either an equally good fit with a double-power law at z ∼ 8 (Finkelstein et al 2015b), or a preference for the double power law at z ∼ 7 (Bowler et al 2014;Bowler et al 2015; but note that the z ∼ 7 investigations are based on ground, rather than space observations). Irrespective of the form of the LF at the bright-end, whose evolution might be linked to changing astrophysical conditions of high-redshift galaxies, such as reduced feedback at early times (Somerville et al 2008), it is clear that overall, the observed population of galaxies (M AB ∼ < − 17) at z > 7 does not produce sufficient photons to ionize the universe.…”
Section: Introductionmentioning
confidence: 96%